Peran Senan Prolanis dalam Menurunkan Kadar Gula Darah pada Pasien Diabetes Melitus Tipe 2 di Puskesmas Kuta Baro Kabupaten Aceh Besar - Meylia Safira; Rosalia Putri; Noeroel Arham (Pusat riset dan Inovasi Nasional, 2026)
The body may experience insulin resistance or an insufficient production of the hormone, blood sugar levels rise continuously, leading to a chronic metabolic condition called Type 2 Diabetes Mellitus. Among non-pharmacological approaches proven effective in managing hyperglycemia, physical exercise particularly the Prolanis workout program has shown notable benefits. This study assesses how joining the Prolanis Exercise Program influences blood glucose reduction in Type 2 Diabetes patients at Kuta Baro Health Center, Aceh Besar. This research utilized a quasi-experimental method applying a one-group pretest–posttest framework. Participants, numbering 25 individuals, were selected through an accidental sampling process.. Throughout a four-week implementation of the Prolanis Exercise Program, measurements of blood glucose levels were taken both prior to and subsequent to the program. The findings revealed a notable decline in mean blood sugar levels, decreasing from 158.84 mg/dL before the intervention to 121.92 mg/dL afterward. Based on the Paired Samples t-Test (p < 0.05), the Prolanis Exercise intervention was found to have a significant effect in lowering blood glucose levels. This finding demonstrates that regular participation in Prolanis Exercise serves as an effective non-pharmacological approach for controlling Type 2 Diabetes Mellitus. Community Health Centers are advised to consistently continue developing and facilitating routine Prolanis Exercise activities, in addition to providing ongoing education on healthy lifestyles to patients. Patients are expected to actively engage in this program as part of their diabetes self-management.